Um estudo sobre os impactos das ações do PIBID nos cursos de licenciatura em química da UFS e do IFS - Santos, Lais Menezes Cardoso dos (2016)
This paper presents some notes resulted from a research about minor teacher formation from the perspective of public policy. The chosen definition in this research about the pedagogical processes is the Institutional Scholarship Program Teaching Introduction (PIBID, in Portuguese). We look forward to understand the impact on the process of the training of undergraduate students from the course of Chemistry of the Federal University of Sergipe (UFS)/Campus São Cristóvão and from the Federal Institute of Sergipe (IFS)/Campus Aracaju, entering the Edital No. 061/2013/CAPES. This objective involves creating opportunities to reflecte about the initial teacher training, the training needs to teach chemistry from the eye of the understandings made by different subjects on the PIBID. To achieve the proposed objective, we analyse and discuss the actions taken by PIBID from the sub-projects of the two institutions already mentioned, polling reviews and semi-structured interviews in which proceeded a discursive textual qualitative analysis. The relevance of the study is given by the recent implementation of the program in the country, encouraging its maintenance, retention and expansion, and the creation of new proposals involving undergraduate students and highlighting the teaching profession. The results showed that the PIBID has a positive impact as it is understood by schools as a breakthrough in the initial training for more intense experience with the school reality and as a reflection on the teaching profession by producing new approaches and different teaching materials for teaching chemistry and for professional development.